Congenital double-orifice mitral valve associated with atrioventricular septal defect: a case report - Küçükosmanoğlu, Osman; Özbarlas, Nazan; Salih, Orhan Kemal (The Turkish Journal of Pediatrics, 2002)
The case of an eight-year-old girl with congenital double-orifice mitral valve associated with atrioventricular septal defect is reported. This rare mitral valve anomaly was diagnosed with two-dimensional echocardiography. The associated atrioventricular septal defect was repaired successfully. The central fibrous bridge between anterior and posterior mitral valve leaflets was left undivided to avoid iatrogenic mitral regurgitation. Preoperative diagnosis may provide some useful information to the surgeon. The surgical method can be individualized in each case.
Keywords: double-orifice mitral valve; atrioventricular septal defect; echocardiography